CT perfusion improves diagnostic accuracy and confidence in acute ischaemic stroke. Issue 6 (25th January 2013) - Campbell, Bruce C V; Weir, Louise; Desmond, Patricia M; Tu, Hans T H; Hand, Peter J; Yan, Bernard; Donnan, Geoffrey A; Parsons, Mark W; Davis, Stephen M
Abstract : Background and objective: CT perfusion (CTP) is rapid and accessible for emergency ischaemic stroke diagnosis. The feasibility of introducing CTP and diagnostic accuracy versus non-contrast CT (NCCT) in a tertiary hospital were assessed. Methods: All patients presenting <9 h from stroke onset or with wake-up stroke were eligible for CTP (Siemens 16-slice scanner, 2×24 mm slabs) unless they had estimated glomerular filtration rate (eGFR)<50 ml/min or diabetes with unknown eGFR. NCCT was assessed by a radiologist and stroke neurologist for early ischaemic change and hyperdense arteries. CTP was assessed for prolonged time to peak and reduced cerebral blood flow. Technical adequacy was defined as 2 CTP slabs of sufficient quality to diagnose stroke. Results: Between January 2009 and September 2011, 1152 ischaemic stroke patients were admitted, 475 (41%) were <9 h/wake-up onset. Of these, 276 (58%) had CTP. Reasons for not performing CTP were diabetes with unknown eGFR (48 (10%)), known kidney disease (36 (8%)), established infarct on NCCT (27 (6%)), posterior circulation syndrome (25 (5%)) and patient motion/instability (16 (3%)). Clinician discretion excluded a further 47 (10%). CTP was more frequently diagnostic than NCCT (80% vs 50%, p<0.001). Non-diagnostic CTP was due to lacunar infarction (28 (10%)), infarct outside slab coverage (21 (8%)), technical failure (4 (1%)) and reperfusion (2 (0.7%)). Normal CTP in 86/87 patients with stroke mimics supported withholding tissue plasminogen activator. CTP technical adequacy improved from 56% to 86% (p<0.001) after the first 6 months. Median time for NCCT/CTP/arch-vertex CT angiogram (including processing and interpretation) was 12 min. No clinically significant contrast nephropathy occurred. Conclusions: CTP in suspected stroke is widely applicable, rapid and increases diagnostic confidence.